Effect of Iron Ion on Corrosion Behavior of Inconel 625 in High-Temperature Water. (22nd October 2020) - Zhou, Huiling; Chen, Yipeng; Sui, Yi; Lv, Yunfei; Zhu, Zhiyuan; Yang, Lanlan; He, Zhen; Li, Chengtao; Fang, Kewei
Abstract : The corrosion behavior of an ultralow iron nickel-based alloy Inconel 625 under high-temperature water has been evaluated. The results show that surface oxidation and pitting were the principal corrosion mechanisms of Inconel 625 during the initial immersion period. The surface layer of the oxide film is first Ni-enriched and then Fe-enriched as immersion time increases. The iron ions dissolved from the autoclave could lead to the formation of NiFe2 O4 and have a great influence on the oxidation behavior of Inconel 625. The oxides nucleated by solid-state reactions with selective dissolution of Fe and Ni and then grew up through precipitation of cations from solution.